Influence of mechanical instruments on creating root canal aberrations - Koprowicz, Agata; Łęski, Michał; Koprowicz, Piotr; Pawlicka, Halina (Journal of Stomatology, 2015)
Introduction. The purpose of the mechanical preparation of the root canal is to enlarge the canal and create a continuously tapering funnel form, from the coronal access cavity to the root apex, as well as to maintain the original canal shape and apical foramen in their original spatial relationship both to the periapical tissues and to the root surface. In the case of curved canals, pre-curved or flexible files, which adapt to the canal curvature, should be used. Failure to observe this rule is the most common cause of straightening the canal and committing procedural errors in the apical part such as formation of ledges, artificial constrictions called elbows, apical zips, fractures of the apical portion of the canal wall or formation of via falsa located at some distance from the anatomical apical foramen. Aim of the study. To evaluate the impact of working movement of files on transportation of the apical foramen, its diameter and the presence of aberrations in the canal’s course. Material and methods. The study involved reciprocating files, WaveOne (Dentsply Maillefer) and Reciproc (VDW), and rotary ProTaper Next system (Dentsply Maillefer). Thirty resin blocks (Endo-Training-Bloc, Dentsply Maillefer) with hollow inside canals containing a single curvature (L-type canals) were used in the study. Prior to preparation, the working length of the canals was measured and then the canals were filled with black ink (Astra SA). After preparation, the blocks were fixed again and photographed. Images were superimposed in a computer software and measuring points were determined. The amount of removed material corresponded to the distance between the measuring point and the wall of the canal after the preparation. The obtained data were subjected to statistical analysis. Results. This study has confirmed the scientists’ opinions that differences in the structure and working movement of files affect the resulting shape of the root canal. The tested instruments ensure simulated canal preparation in a satisfactory manner. The concept of one file with high and variable taper carries the risk of more extensive canal transportation. However, the comparison of the preparation with the system based on a sequence of files did not reveal any statistically significant differences.